Purification and pharmacokinetic study of gadoxetate isomers for enhanced rabbit liver MR imaging - Yiling Chang; Qilin Li; Man Yi; JiGen Li; Xiaodong Yuan (PLoS ONE, 2026)
This study aimed to purify and prepare two isomers of Gadoxetate (Gd-A and Gd-B) from Pumexian and evaluate their stability, magnetic resonance (MR) imaging characteristics, and pharmacokinetics in rabbits. Reversed-phase liquid chromatography was employed to separate Gd-A and Gd-B, achieving purities exceeding 99% for both isomers. These purified isomers were then processed into vacuum-encapsulated solid powders via nitrogen blowing and freeze-drying. Stability assessments were conducted by storing the powders at various temperatures (25°C, −20°C, 50°C, and 80°C) for two months. The results indicated high stability at room temperature (25°C) and low temperature (−20°C), with both Gd-A and Gd-B maintaining 99% purity. At higher temperatures, purity slightly decreased: Gd-A was 98% at 50°C and 95% at 80°C, while Gd-B was 97% at 50°C and 94% at 80°C. For the in vivo evaluation, twelve rabbits were randomly assigned to two groups and received intravenous bolus injections of either pure Gd-A or Gd-B, followed by enhanced MR scanning and serial blood sampling. Pharmacokinetic and imaging analyses revealed statistically significant differences (p < 0.05) between the two isomers. Specifically, Gd-A exhibited a shorter time to peak enhancement in liver parenchyma (t peak A < t peak B), higher peak signal intensity in the liver parenchyma (SI peak A > SI peak B), greater plasma clearance (PCL-A > PCL-B), and a shorter half-life (t 1/2 A < t 1/2 B) compared to Gd-B. In conclusion, the vacuum-encapsulated solid powders of Gd-A and Gd-B demonstrate good long-term stability at room or low temperatures while maintaining high purity. Furthermore, the distinct pharmacokinetic profile and imaging characteristics of pure Gd-A suggest its potential value for clinical applications.